Differential Contribution of Constituent Metal Ions to the Cytotoxic Effects of Fast-Dissolving Metal-Oxide Nanoparticles - Jeong, Jiyoung; Kim, Sung-Hyun; Lee, Seonghan; Lee, Dong-Keon; Han, Youngju; Jeon, Soyeon; Cho, Wan-Seob (Frontiers in Pharmacology, 2018)
The main mechanism of toxicity for fast-dissolving nanoparticles (NPs) is relatively simple as it originates from the intrinsic toxicity of their constituent elements rather than complicated surface reactivity. However, there is little information about the compared toxicity of fast-dissolving NP and its constituent ion, which is essential for understanding the mechanism of nanoparticle toxicity and the development of a structure-toxicity relationship model. Herein, we selected three types of fast-dissolving metal-oxide NPs (CoO, CuO, and ZnO) and constituent metal chlorides (CoCl2, CuCl2, and ZnCl2) to compare dose-response curves between NP and its constituent metal. These materials were treated relevant cell lines for inhalation setting (i.e., differentiated THP-1 cells for macrophages and A549 cells for alveolar epithelial cells) and cytotoxicity as an endpoint was evaluated at 24 hr post-incubation. The results showed that CoO and CuO NPs in both cell types showed similar patterns of dose-response curves and cytotoxic potential compared to that of their respective metal chloride. On the other hand, ZnO NPs in both cell types showed a completely different dose-response curve compared to that of ZnCl2: ZnO NPs showed modest slope and much less potential for cytotoxicity compared to that of ZnCl2. These results imply that fast-dissolving metal-oxide NPs are not always have similar dose-response curves and toxic potentials compared to their constituent metal chlorides and this may be due to the differential mechanism of intracellular uptake of these substances and their interaction with intracellular detoxification molecules. Further investigations are needed for the use of toxic potential of metal ions as a predicting factors of fast-dissolving NPs toxicity. In addition, chelating agent specific for dissolved metal ions can be applied for the treatment of these fast-dissolving NPs.